Be nice to your innovators: Employee treatment and corporate innovation performance - Chen, Chen; Chen, Yangyang; Hsu, Po-Hsuan; Podolski, Edward J. (Journal of Corporate Finance, 2016)
This paper investigates the effect that employee treatment schemes have on corporate innovation performance. We find that firms with better employee treatment schemes produce more and better patents through improving employee satisfaction and teamwork. Additional tests suggest that our main findings cannot be attributed to job security, unionization, reverse causality, and omitted variables. We also find that firms with better employee treatment schemes produce patents that enhance market valuation and facilitate better future operating performance. Collectively, our findings show that treating employees well benefits firms and shareholders, for well treated employees are encouraged to create intellectual property.